Microstructure and mechanical properties of hammer-forging assisted wire-arc directed energy deposition AZ91 alloy - Fangyong Niu; Cunxu Li; Lu Li; Mingze Xu; Yunbo Hao; Kai Zhao; Huanyue Zhang; Guoping Liu; Guangyi Ma; Dongjiang Wu (Virtual and Physical Prototyping, 2024)
With the development of lightweight aerospace equipment, magnesium alloys are receiving increasing attention. Wire-arc directed energy deposition (Wire-arc DED) is a highly promising manufacturing method for magnesium alloy parts, but its development has been severely restricted by the problems of coarse grain size and low mechanical properties. To address these issues, a hammer-forging assisted Wire-arc DED technology for magnesium alloy AZ91 is proposed. The effects of interlayer hammer-forging and synchronous hammer-forging on macrostructure, microstructure and mechanical properties of the Wire-arc DED samples are compared, and the microstructure evolution and performance enhancement mechanism are discussed. The results show that the maximum plastic deformation caused by hammer forging reaches 11.7%. Hammer forging can significantly refine grains, and the average grain size decreases from 27.7 μm to 13.5 μm. Synchronous hammer-forging is better than interlayer hammer-forging in terms of performance enhancement, the UTS reaches 301.8 MPa, an increase of 10.9%, which is comparable to that of traditional forged parts, mainly attributed to the grain refinement and increased dislocation density.